Chloroplast genome variation and phylogenetic relationships of Atractylodes species - Yiheng Wang; Sheng Wang; Yanlei Liu; Qingjun Yuan; Jiahui Sun; Lanping Guo (BMC Genomics, 2021)
Abstract Background Atractylodes DC is the basic original plant of the widely used herbal medicines “Baizhu” and “Cangzhu” and an endemic genus in East Asia. Species within the genus have minor morphological differences, and the universal DNA barcodes cannot clearly distinguish the systemic relationship or identify the species of the genus. In order to solve these question, we sequenced the chloroplast genomes of all species of Atractylodes using high-throughput sequencing. Results The results indicate that the chloroplast genome of Atractylodes has a typical quadripartite structure and ranges from 152,294 bp (A. carlinoides) to 153,261 bp (A. macrocephala) in size. The genome of all species contains 113 genes, including 79 protein-coding genes, 30 transfer RNA genes and four ribosomal RNA genes. Four hotspots, rpl22-rps19-rpl2, psbM-trnD, trnR-trnT (GGU) , and trnT (UGU) -trnL, and a total of 42–47 simple sequence repeats (SSR) were identified as the most promising potentially variable makers for species delimitation and population genetic studies. Phylogenetic analyses of the whole chloroplast genomes indicate that Atractylodes is a clade within the tribe Cynareae; Atractylodes species form a monophyly that clearly reflects the relationship within the genus. Conclusions Our study included investigations of the sequences and structural genomic variations, phylogenetics and mutation dynamics of Atractylodes chloroplast genomes and will facilitate future studies in population genetics, taxonomy and species identification.